Análise da estabilidade global de um edifício variando o fck do concreto dos pilares e o número de pavimentos da edificação - Tatto, Igor Felipe (2025)
With the verticalization of urban centers, accompanied by an increase in the slenderness of the elements, it is necessary to understand the analysis of global stability, aiming at structural safety, considering, among other aspects, the deformations in the structure. With this in mind, this work focuses on studying the influence of the characteristic compressive strength of concrete (fck) and the height of the building on the global stability of reinforced concrete buildings, analyzing the stability parameter γz and the horizontal displacements in the structure. To carry out this study, TQS software was used, along with the application of concepts relating to global stability, such as physical and geometric non-linearities and the consideration of horizontal and vertical actions, in accordance with national standards. Initially, a building model was analyzed with respect to varying the number of floors, changing the fck of the columns in four classes, considering concretes C30, C40, C50 and C60. Subsequently, a second analysis was carried out, comparing the reduction of the central columns of the 9 floors model with regard to global stability and the quantities of material in an isolated column. The results showed an increase in global stability, with more significant values for the 12 floors models, and a reduction in displacements with the use of higher concrete classes, around 25% for displacements at the top of the building with the use of C60 concrete, compared to C30 concrete. A reduction in the amount of steel in the columns was also observed, with the best results for the model using class C50 concrete, with reductions of more than 50% in the amount of steel in the central columns of the structure, also compared to C30 concrete.